Diversity of the ‘Eerie’ Glass Squid Genus Taonius Steenstrup, 1861 (Cephalopoda: Oegopsida) in the Pacific Ocean - Evans, A; Voss, N; Braid, H; Kubodera, T; Bolstad, K (Informa UK Limited, 2024)
‘Glass’ squids (family Cranchiidae Prosch, 1849) are diverse and widely distributed, but many cranchiid genera are in need of global taxonomic revision. Although two species of Taonius are generally recognised from the Pacific Ocean (T. belone and T. borealis), a recent review of material from this basin has revealed the presence of at least six species, including at least four new to science, described here as T. expolitus, T. notalia, T. robisoni, and T. tanuki. Morphological species identities are supported by several characters, including arm sucker count, and arm and manus sucker dentition. Proposed species delimitations are further supported by differences in mitochondrial DNA (cytochrome c oxidase subunit I). Although a full systematic review of the Cranchiidae is still needed tripling the known diversity of Taonius in the Pacific Ocean and clarifying identities of its locally occurring species represent an important step forward.
Keywords: 31 Biological Sciences; 3103 Ecology; 3104 Evolutionary Biology; 0608 Zoology; Ecology; 3109 Zoology